Law No. 14 for Year 2018 on Renewing Applying Law No. 79 for Year 2016 On Settlement of Tax Disputes and Amending Certain Provisions Thereof = قانون رقم 14 لسنة 2018 بتجديد العمل بالقانون رقم 79 لسنة 2016 فى شأن إنهاء المنازعات الضريبية وتعديل بعض أحكامه - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic